(untitled) (Journal of Forensic Medicine & Toxicology, 2012)
Domestic violence has presently drawn maximum attention in our country where male dominated society is predominant. However women undergo as much agony in the dominantly matrilineal tribal societies in Meghalaya, as their counterpart in the rest of the country. Majority of the victims were in the age group of 20 to 30 years. Tribals constitute 69.23 % of the cases; more in rural areas. The perpetrators were mostly the husbands. 61.54% of the perpetrators were alcoholics. The commonest assault was physical abuse. Socio-cultural factors associated with such violence need to be addressed to prevent such crimes.